Characterization of the Conformational Equilibrium between the Two Major Substates of RNase A Using NMR Chemical Shifts. - Camilloni,C; Robustelli,P; De,Simone A; Cavalli,A; Vendruscolo,M (J Am Chem Soc, 2012)
Following the recognition that NMR chemical shifts can be used for protein structure determination, rapid advances have recently been made in methods for extending this strategy for proteins and protein complexes of increasing size and complexity. A remaining major challenge is to develop approaches to exploit the information contained in the chemical shifts about conformational fluctuations in native states of proteins. In this work we show that it is possible to determine an ensemble of conformations representing the free energy surface of RNase A using chemical shifts as replica-averaged restraints in molecular dynamics simulations. Analysis of this surface indicates that chemical shifts can be used to characterize the conformational equilibrium between the two major substates of this protein.